Reading and writing Chinese : a comprehensive guide to the Chinese writing system - McNaughton, William, 1933- (Tuttle, 2013)
"Reading & Writing Chinese places at your fingertips the essential 1,725 Chinese characters' up-to-date definitions, derivations, pronunciations, and examples of correct usage by means of cleverly condensed grids. This guide also focuses on Pinyin, which is the official system to transcribe Hanzi, Chinese characters, into Latin script, now universally used in mainland China and Singapore. Traditional characters (still used in Taiwan and Hong Kong) are also included, making this a complete reference. Newly updated and revised, these characters are the ones officially prescribed by the Chinese government for the internationally recognized test of proficiency in Chinese, the Hanyu Shuiping Kaoshi (HSK)"--Publisher's website